CenteringPregnancy group prenatal care: Promoting relationship-centered care. - Massey, Zohar; Rising, Sharon Schindler; Ickovics, Jeannette (Journal of obstetric, gynecologic, and neonatal nursing : JOGNN / NAACOG, 2006)
CenteringPregnancy is an innovative model of group prenatal care that has been implemented at more than 100 prenatal care sites since 1995. CenteringPregnancy provides group prenatal care that is relationship centered, nurturing and transforming relationships among women, their families, and health care professionals. Complete prenatal care is provided in a group setting. Prenatal assessment, education, and support occur in a facilitative environment. The model offers effective and efficient care that is sustainable and can enhance the health of women, their families, health care providers, and communities.
Keywords: Evidence-Based Medicine; Family; Health Promotion; Health Services Needs and Demand; Humans; Institute of Medicine (U.S.); Interpersonal Relations; Maternal-Child Nursing; Models, Nursing; Models, Organizational; Mothers; Nursing Assessment; Outcome and Process Assessment (Health Care); Patient Education as Topic; Patient-Centered Care; Peer Group; Prenatal Care; Program Evaluation; Randomized Controlled Trials as Topic; Self-Help Groups; Social Support; United States